2015
DOI: 10.1007/s10826-015-0276-6
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Problems that Mediate Treatment Utilization Among Children in Foster Care

Abstract: Children in foster care suffer from an extremely high prevalence of mental health problems, yet, it remains unclear if they consistently use mental health treatments, such as therapy. To determine whether these children receive treatment more often when they have specific types of mental health problems, we examined the prevalence and associations between mental health problems, as identified by standardized screening, and mental health treatment utilization. Using descriptive statistics, multivariate models, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
0
8
0
1
Order By: Relevance
“…In addition to having difficulty forming peer relationships, foster youth are also identified as having higher levels of peer problems than comparison groups (e.g., Millward, Kennedy, Towlson, & Minnis, 2006). Furthermore, a large proportion of foster youth are identified as having levels of peer problems warranting clinical intervention (Conn, Szilagyi, Alpert-Gillis, Baldwin, & Jee, 2015;Minnis, Everett, Pelosi, Dunn, & Knapp, 2006). Foster youths' peer relationships are often characterized by negative behaviors (M. C. Smith, 1995) and perceived as being lower quality (Flynn, Ghazal, Legault, Vandermeulen, & Petrick, 2004;Stein, 1997).…”
Section: Importance Of Peer Relationshipsmentioning
confidence: 99%
“…In addition to having difficulty forming peer relationships, foster youth are also identified as having higher levels of peer problems than comparison groups (e.g., Millward, Kennedy, Towlson, & Minnis, 2006). Furthermore, a large proportion of foster youth are identified as having levels of peer problems warranting clinical intervention (Conn, Szilagyi, Alpert-Gillis, Baldwin, & Jee, 2015;Minnis, Everett, Pelosi, Dunn, & Knapp, 2006). Foster youths' peer relationships are often characterized by negative behaviors (M. C. Smith, 1995) and perceived as being lower quality (Flynn, Ghazal, Legault, Vandermeulen, & Petrick, 2004;Stein, 1997).…”
Section: Importance Of Peer Relationshipsmentioning
confidence: 99%
“…Erickson and colleagues referred to their mediation analysis as exploratory due to an inability to establish a temporal precedence between the levels of brain-derived neurotrophic factor and hippocampal deterioration (Erickson et al, 2010). Finally, in their study of mental health treatment utilization for children in foster care, Conn et al used the term to denote post-hoc analyses done to test hypotheses derived after conducting other statistical tests (Conn, Szilagyi, Alpert-Gillis, Baldwin, & Jee, 2016). …”
Section: Exploratory Mediation Analysismentioning
confidence: 99%
“…The unpredictable and traumatic events that adolescents, particularly girls in the foster care and juvenile justice system, experience precede their placement in out‐of‐home care (e.g., residential care programs) and often leads to emotional and behavioral problems (Conn, Szilagyi, Alpert‐Gillis, Baldwin, & Jee, ). Many studies have shown that in general, youth in the foster care (Conn et al., ; Jones, ; Tarren‐Sweeney, ) and juvenile justice system (Callahan, Cocozza, Steadman, & Tillman, ; Vincent, Grisso, Terry, & Banks, ) exhibit higher rate of behavior problems and academic risks relative to their peers in the general population. In a representative sample of 230 adolescents residing in foster care, Tarren‐Sweeney () reported that about half of adolescents in foster care have mental health problems that require referral to treatment services.…”
Section: Residential Care: Education and Treatmentmentioning
confidence: 99%